Experimental and modeling investigation on separation of methane from coal seam gas (CSG) using hydrate formation. (1st May 2018) - Wang, Yiwei; Deng, Ye; Guo, Xuqiang; Sun, Qiang; Liu, Aixian; Zhang, Guangqing; Yue, Gang; Yang, Lanying
Abstract: The effects of temperature, pressure, initial promoter concentration and coal seam gas/liquid ratio on the separation of methane from coal seam gas were experimentally investigated. Low temperature, high pressure and high promoter concentration lead to high separation efficiency and high recovery rate of CH4, but reduce the CH4 capture selectivity in hydrate. Experimental simulation of a three-stage separation shows that CH4 can be concentrated from 34.6 to 81.3 mol% in the dissociated gas, while its content is only 7.2 mol% in the residual gas. An innovative model was established to predict the separation performance. The modeling results reasonably match the experimental data in predicting the effects of different influential factors, with an average relative deviation of 2.83%, the maximum relative deviation 11.2%, and the average relative variance 0.1044. The modeling results of a three-stage separation process include 81.0 mol% of CH4 in the final dissociated gas and 5.5 mol% of CH4 in the final residual gas. The recovery rate of CH4 was 90.1 mol% and the separation factor was 73.0. Highlights: A model was proposed to predict the hydrate based separation performance. CH4 can be concentrated from 34.6 to 81.3 mol% in dissociated gas. CH4 content can be reduced from 34.6 to 7.2 mol% in residual gas. High pressure, low temperature, high TBAB concentration favor high CH4 recovery. Modeling shows that 90.1% CH4 can be recovered from CSG after multistage separation.